Ethnopedagogy of STAI Denpasar Bali in Juz 30 Memorizing Course Balinese Language Translation: Actualization of Local Wisdom Values - Rusmayani, Rusmayani; Ramdhani, Fajri Zulia; atussolihah, Badi' (Jurnal Ilmu Pendidikan, 2022)
STAI (Islamic Higher Education) Denpasar Bali is the only Islamic religious college in Denpasar City. As a university located among most of the Hindu community, this institution has a special course, namely memorizing section 30 of Al-Qur'an in Balinese translation, as a form of implementation of an ethnopedagogy approach. This study aims to describe the ethnopedagogy of STAI Denpasar Bali during section 30 of Al-Qur'an memorization in Balinese translation. This study used the descriptive qualitative method, and the data was collected through unstructured interviews with informants. For the informants, we involved the Head of STAI Denpasar Bali, the Head of the Academic Sector, the coordinator of memorizing section 30 of the Al-Qur'an course, the lecturer of the Al-Qur'an to Balinese translation course, students, relevant stakeholders, and Aswaja Dewata as well as the General Chair of the Indonesia Clerical Council (MUI) in Bali. Our findings suggested that 1) this course has only been implemented for two years since 2020 to participate in preserving local wisdom and symbols of the Islamic religion in Bali. In practice, this course consists of memorizing section 30 of Al-Qur'an, and translations in Balinese, which are carried out at different times and by different tutors, 2) Ethnopedagogy in the Qur'an section 30 translation course of Balinese language is taught by internalizing cultural values and language levels, and 3) actualization of Balinese language in the Qur'an section 30 Balinese language aim to recultivate the recently degraded Balinese language